The prevalence rates and sequelae of delirium at age older than 90 years. Issue 5 (October 2021) - Gehrke, Samuel; Bode, Leonie; Seiler, Annina; Ernst, Jutta; von Känel, Roland; Boettger, Soenke
Abstract: Objective: Although age and pre-existent dementia are robust risk factors for developing delirium, evidence for patients older than 90 years is lacking. Therefore, this study assesses the delirium prevalence rates and sequelae in this age group. Method: Based on a Diagnostic and Statistical Manual (DSM)-5, Delirium Observation screening scale (DOS), and Intensive Care Delirium Screening Checklist (ICDSC) construct, in this prospective cohort study, the prevalence rates and sequelae of delirium were determined in 428 patients older than 90 years by simple logistic regressions and corresponding odds ratios (ORs). Results: The overall prevalence delirium rate was 45.2%, with a wide range depending upon specialty: intermediate and intensive care services (83.1%), plastic surgery and palliative care (75%), neurology (72%), internal medicine (69%) vs. dermatology (26.5%), and angiology (14.5%). Delirium occurred irrespective of age and gender; however, pre-existent dementia was the strongest delirium predictor (OR 36.05). Delirious patients were less commonly admitted from home (OR 0.47) than from assisted living (OR 2.24), indicating functional impairment. These patients were more severely ill, as indicated by emergency (OR 3.25) vs. elective admission (OR 0.3), requirement for intensive care management (OR 2.12) and ventilation (OR 5.56–8.33). At discharge, one-third did not return home (OR 0.22) and almost half were transferred to assisted living (OR 2.63), or deceased (OR 47.76). Significance of results: At age older than 90 years, the prevalence and sequelae of delirium are substantial. In particular, functional impairment and pre-existent dementia predicted delirium and subsequently, the loss of independence and death were imminent.